NIKAH MUHALLIL PERSPEKTIF EMPAT MADZHAB - Maryam Qurotul Aini, Siti; Ainiyah, Hilmi Huriyatul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
This article aims to reveal the views of the imams of the four schools of thought. The approach used is normative. Muhallil marriage is a marriage that is carried out to justify a person who has done triple talaq to immediately return to his wife with a new marriage. If a person has divorced his wife three times, either in one period or at different times, then the husband may no longer marry his ex-wife unless the wife has married another man, then divorces and her iddah expires. The purpose of marrying another man is not just doing a marriage contract, but having sexual relations as is the case for husband and wife life in general, then divorcing him properly so that the first husband can marry his ex-wife.